Madness in Post-1945 British and American Fiction - Baker, C. author. aut Link
XI, 223 p.
Keywords: A comprehensive and thematic exploration of representations of madness in postwar British and American Fiction, this book is relevant to those with interests in literary studies and is a vital read for psychiatric clinicians and professionals who are interested in how literature can inform and enhance clinical practices.